Ambient atmosphere-processable, printable Cu electrodes for flexible device applications: structural welding on a millisecond timescale of surface oxide-free Cu nanoparticles1. Issue 9 (4th March 2015) - Oh, Sang-Jin; Jo, Yejin; Lee, Eun Jung; Lee, Sun Sook; Kang, Young Hun; Jeon, Hye-Ji; Cho, Song Yun; Park, Jin-Seong; Seo, Yeong-Hui; Ryu, Beyong-Hwan; Choi, Youngmin; Jeong, Sunho
<x xml:space="preserve">Abstract</x> We demonstrate Cu nanoparticle-derived printed conductive structures on plastic and paper substrates in air.